THE ROLE OF INTERNATIONAL LAW IN PROTECTING AFGHAN ASYLUM SEEKERS AND AFGHAN REFUGEES IN IRAN - Ali Ahmad Mowahid; Fazl Ahmad Ahmadi (International Journal of Law in Changing World)
Iran, being a neighbouring and easily accessible country, has been the primary host of Afghan refugees for the last four decades. Although Afghan asylum seekers have been living in the country for a long time, they are provided with minimal human rights protection. This article examines international documents, laws, and regulations related to asylum seekers and refugees. It explores the status of asylum seekers and refugees in international law, focusing on Afghan asylum seekers in Iran. This research has been conducted using a descriptive-analytical method to the following research question: To what extent has international law and its related instruments been effective in enhancing protections and improving the situation of Afghan refugees in Iran? The findings reveal that, although international law has provided protective frameworks, it has not been able to compel Iran to respect the rights of Afghan asylum seekers. Domestic policies, economic conditions, and the lack of binding legal instruments have posed hindrances to effectively implementing these commitments.